Quantitative validation of nicotine production in tea (Camellia sinensis L.). - Takashi Ikka; Hiroto Yamashita; Ikuya Kurita; Yasuno Tanaka; Fumiya Taniguchi; Akiko Ogino; Kazuya Takeda; Nobuhiro Horie; Hiroshi Hojo; Fumio Nanjo; Akio Morita (PLoS ONE, 2018)
Endogenous nicotine was confirmed to be present in tea plants (Camellia sinensis L.) by liquid chromatography-tandem mass spectrometry of tea samples from tea-producing regions in six Asian countries. All samples contained nicotine (0.011-0.694 μg g-1 dry weight). Nicotine contents remained constant during manufacturing of green, oolong and black teas, implying that nicotine is stable against heating, drying, enzymatic oxidation and mechanical damage during processing. Flower buds and seeds of cultivar Yabukita also contained nicotine (0.030-0.041 μg g-1 dry weight). A comparison of two cultivars revealed that higher nicotine contents were found in the black tea cultivar Benifuki. All plant parts of hydroponic Yabukita contained nicotine (0.003-0.013 μg g-1 dry weight). Tea cells cultured in B5 medium as well as roots and stems of tea seedlings contained nicotine levels similar to those of new leaves from field-grown plants. Although the levels of endogenous nicotine in tea plants are extremely low and sample contamination cannot be discounted, these levels exceed the maximum acceptable limit in Japan (0.01 μg g-1 dry weight).